ANALISIS KEPUASAN DOSEN FAKULTAS EKONOMI DAN BISNIS TERHADAP UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Saragih, Nawary; Sihotang , Helena (UNIKA Santo Thomas, 2024)
This research aims to assess lecturer satisfaction at the Faculty of Economics and Business, Santo Thomas Catholic University, Medan. Utilizing a descriptive and quantitative approach, the study includes 36 respondents selected through census sampling. Data collection employed a questionnaire via a Google Form link, and the analysis method used is descriptive. Results reveal that the dimension of Research and Scientific Work signifies strong satisfaction (scale 4) among lecturers, with the highest score of 76.04% out of the 9 studied dimensions. Competency Development, Career/Position Development, Community Service (PkM), Library Services, Administrative Services, Additional Tasks, Welfare Needs, and Social/Religious Needs register satisfaction at scale 3 (Fair/Medium), ranging from 0.50% to 0.75%. Dissatisfaction levels are weak/low, below 0.50%. Recommendations include improving elements related to Research and Scientific Work, which are currently at scale 4. Additionally, efforts are needed to enhance satisfaction levels in Competency Development, Career/Position Development, Community Service (PkM), Library Services, Administrative Services, Additional Tasks, Welfare Needs, and Social/Religious Needs, aiming for scale 4 and 5.